Perancangan Rumah Sakit Jiwa Di Kabupaten Merauke - Mario Pati F. Renyaan; Yosi Valentina Simorangkir; Anton Topan; Atiza Nurhuzna (Musamus Journal of Architecture, 2023)
Merauke is a city located in the eastern end of Indonesia that also has. Problems with mental disorders. But in Merauke regency itself does not have the facilities and infrastructure of a place for rehabilitation of mental gannguan disease. For this reason, health facilities and infrastructure are needed for people with mental disorders, which meet the standards in accommodating all mental disorders problems in the city of Merauke. The method used in this study is a descriptive method carried out by collecting data in the form of interviews and questionnaires at the Merauke Regency Health office, as well as direct documentation of the research object. In addition, it takes some related data in the form of literature on regulations, standards, books and journals. The results of the data obtained are used for reference in determining the type of space needs and the design of the Mental Hospital building in Merauke Regency. The design of the Mental Hospital in Merauke Regency is in BWK Merauke Regency. The design of this mental hospital in Merauke Regency focuses on the completeness of facilities and infrastructure that are in accordance with martial arts standards. The application and approach of healing environment in this design can be seen in the hospital environment that will implement a lot of Green Open Space.